Managing library automation - Clayton, Marlene (Ashgate, 1992)
"Managing Library Automation" provides a concise, easy-to-read guide to the main factors which librarians and information workers should be aware of when considering computerization. This second edition has been revised and updated with the assistance of Chris Batt to ensure a fresh perspective. The book retains, however, its original brief of not attempting to cover every detail of an extensive topic, but instead, gives the essential facts and indicates significant trends. Historical accounts have been kept to the minimum and no attempt has been made to describe or explain computing techniques except where an understanding of these assists the effective use of systems by librarians. References to further reading are given where appropriate. The book begins by setting library automation within the context of a wider strategy for the use of Information Technology.